Gamified strategies and English grammar learning among superior basic education students at a public institution in Loja, school year 2023-2024 - Valarezo Acaro, Wendy Del Cisne (2024)
The English language has been recognized as a vital tool in the educational field since it provides students with the necessary models to structure words and sentences, facilitating accurate, meaningful, and adequate communication. This research aimed to analyze the contribution of gamified strategies in English grammar to students of higher basic education at a public institution in Loja, school year 2023-2024. Based on the role highlighted by grammar and the positive impact of gamification, the study involved 35 participants chosen by convenience sampling using a mixed methods approach to analyze the qualitative and quantitative data coming from the pre- and post-test of the instrument, questionnaire, and field notes. Through data analysis, it was observed, using descriptive statistics, that the use of gamified strategies generated a slight improvement of 1.61 points compared to the mean pretest and posttest scores. Quantitative pretest and posttest data reveal a slight improvement in students' grammatical comprehension skills. Qualitative insights, gathered through a questionnaire with open-ended questions and the researcher's field observations, highlight students' perspectives on the benefits of gamified strategies. These data were examined through thematic analysis, and the results revealed a general acceptance by the students of the established strategy. The study concluded that students' positive perceptions highlight the potential for creating an enjoyable learning environment, emphasizing the continued importance of exploring and implementing gamification in language teaching. Keywords: English grammar, gamified strategies, positive impact, student perception.